2011
DOI: 10.1073/pnas.1106448108
|View full text |Cite
|
Sign up to set email alerts
|

Independent modulation of the kinase and polo-box activities of Cdc5 protein unravels unique roles in the maintenance of genome stability

Abstract: Polo-like kinases (PLKs) are evolutionarily conserved kinases essential for cell cycle regulation. These kinases are characterized by the presence of a C-terminal phosphopeptide-interaction domain, the polo-box domain (PBD). How the functional domains of PLKs work together to promote cell division is not understood. To address this, we performed a genetic screen to identify mutations that independently modulate the kinase and PBD activities of yeast PLK/Cdc5. This screen identified a mutagenic hotspot in the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 51 publications
1
50
0
Order By: Relevance
“…This is clearly the case for some Cdc5 substrates (Yoshida et al 2006). Intriguingly, however, recent analyses indicate that phosphopeptide binding by the Cdc5 PBD is not truly essential, and instead is required for only a subset of Cdc5-dependent processes (Chen and Weinreich 2010;Ratsima et al 2011).…”
Section: The Apc/cmentioning
confidence: 94%
See 1 more Smart Citation
“…This is clearly the case for some Cdc5 substrates (Yoshida et al 2006). Intriguingly, however, recent analyses indicate that phosphopeptide binding by the Cdc5 PBD is not truly essential, and instead is required for only a subset of Cdc5-dependent processes (Chen and Weinreich 2010;Ratsima et al 2011).…”
Section: The Apc/cmentioning
confidence: 94%
“…As discussed in detail below, in essence Cdc5 turns on both pathways and thereby increases the activity of Cdc14 (Figure 8). This is probably triggered by changes in Cdc5 kinase activity rather than in PBD-mediated docking to substrates (Ratsima et al 2011). Intriguingly, since Cdc5 is a robust target of APC Cdh1 in G1 phase, the kinase effectively plants the seeds of its own destruction by upregulating Cdc14 (Visintin et al 2008).…”
Section: The Apc/cmentioning
confidence: 99%
“…In light of the role of Cdc14p in Chs2p export from the ER (Chin et al, 2012), we hypothesized that the Chs2p trafficking defects observed by mutation of CDC5 are caused by defects in release of Cdc14p from the nucleolus. To explore this, we took advantage of a cdc5 mutant strain, cdc5-77 ts , which carries a single amino acid mutation D263Q in the kinase domain resulting in a diminished MEN-induced nucleolar Cdc14p release (Ratsima et al, 2011). Trafficking of Chs2-3xGFP to the bud-neck is also compromised in cdc5-77 ts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were taken at intervals and processed for microscopic characterization of yeast bud, spindle, and nuclear morphology, as described previously (23). Yeast images were acquired on a Leica DM5500B microscope equipped with an EM-CCD camera (Hamamatsu).…”
Section: Yeast Cell Cycle Experimentsmentioning
confidence: 99%
“…Brightness and contrast adjustments were applied to primary micrographs using Photoshop software (Adobe). During time course experiments, yeast culture samples were also processed for determination of DNA content by flow cytometry using published procedures (23).…”
Section: Yeast Cell Cycle Experimentsmentioning
confidence: 99%